(untitled) (Raparin Journal of Humanities (RJH), 2024)
The Assyrians were commercially proficient, and Kurdistan was an important place. Trade in the Kurdistan region was at its peak in the second millennium BC, and Mitanni and Khouri controlled power, politics, and religion. And there was a business plan; archaeological digs revealed the following facts: Kurdistan’s cities were an important trade gate for merchants, and at the same time, in terms of geographical nature, the plains were rich with crops such as wheat, barley, and sesame, and the mountainous areas were important places for grazing animals such as sheep, goats, and cattle, etc., so tribes were going to the Garman and highlands to find pastures for their livestock. However, they brought goods and raw materials abroad through trade, and the goods and supplies they had not touched had brought them abroad. These areas of Kawa trade with Kurdistan, such as southern Mesopotamia, Syria, Anatolia, Iran, Afghanistan, Egypt, and Phoenix, etc., have been disclosed to us according to the text of the business text. Kurdistan’s trade routes were interconnected between east, west, north, and south, and Kurdistan was a trade strategy center. Part of the trade route settled between the mountain ranges as an important trade route, and another part of the trade route also settled between the mountain ranges as an important trade route. The trade routes have been connected between the plains and areas of the cities, or the trade routes of the mountainous areas and the plains are connected to each other, and the construction of foreign trade routes will thus make the business of this area stronger. What was the importance of Kurdistan in terms of trade? The places where Kawa has exchanged trade with Kurdistan What was the importance of Kurdistan in terms of trade? Where were the places where they exchanged trade with Kurdistan? What were the goods and products exported and imported? The most important commodities were the minerals traded abroad and internally? What were those minerals? Kurdistan trades with the outside world because of the richness of its geography?